Cloud Computing Challenges and Opportunities - Abdelghader Morsi, Mohamed; Naji Mahmoud Fadoul, Eman; Mohammed Eshag Ibrahim, Esraa; Mohammed Ibrahim Mohammed, Mehad (University of Khartoum Engineering Journal, 2022)
Abstract: This paper introduces the technology of cloud computing, and the challenges and opportunities associated with it, it also finds solutions for security and high cost issues. In this paper we use open source tools to build an environment for cloud computing, it also solves the aforementioned cloud problems in addition to providing an enormous storage capacity.